Mechanical Degradation of Polypropylene Solutions Under Large Pressure Drops - Martini, Raquel Evangelina (2007)
The degradation of polypropylene (PP), dissolved in n-alkanes at high temperatures and pressures, during the solution discharge to ambient conditions was experimentally studied. Molecular weight distributions (MWD) of the solubilized PP were measured by gel permeation chromatography. The MWD curves of PP obtained after discharge of the polymer solution shift to the low molecular weight side of the distribution and the polydispersity is reduced. In this work, a systematic study on the discharge products was performed to elucidate the degradation mechanism and the effects of temperature and concentration on this phenomenon. Initially, pure polymers, PP and polystyrene (PS) were studied varying the solution temperature. In a second stage, the effect of polymer concentration on chain scission was assessed using experiments on physical blends of PP/PS. In all cases, thermal and oxidative degradation were previously analyzed. Mechanical degradation was found to be the main chain scission mechanism. A negative linear functionality of the chain scission was found in both temperature and polymer concentration. To analyze the relationship between polymer degradation and molecular weight, the chain scission distribution function was calculated. On this basis, a critical molecular weight for the beginning of chain scission was obtained. This value is a function of temperature but remains constant with concentration.